Seismic performance of various structural configurations for RC building on sloped terrain considering soil-foundation-structure approach - Parmar, Dhimant; Ponnappan, Nikhilesh; Thampi, Advaitha; S, Prasanth (Frontiers in Built Environment, 2025)
The study aims to evaluate the seismic performance of reinforced concrete (RC) buildings on slopes using soil–foundation–structure (SFS) interaction modeling. This study investigates the seismic performance of different structural configurations for a five-story RC building on sloped terrain, incorporating bracings, shear walls, grade beams, stub columns, strap footings, and hybrid arrangements. Three critical slope locations—toe, crest, and center—at 20° inclination were analyzed using the SFS modeling approach in PLAXIS 3D, incorporating soil nonlinearity. The RC building was modeled to assess the inter-story drift ratio (ISDR) and lateral displacement as performance parameters. Results indicate that structures on sloping ground were much more vulnerable than those on level ground, with bare-frame structures exhibiting the worst seismic performance at all slope locations. Braced and shear wall buildings show remarkable improvements, with up to 90% reduction in both lateral displacement and inter-story drift ratio compared to typical bare-frame systems and hybrid configurations such as the M26 model, achieving reductions in critical shear force and bending moment exploitation ratios by as much as 2.3× and 1.5×, respectively, at the observed column. At the crest, optimal configurations showed a 91% reduction in lateral displacement. For buildings at the center of the slope, certain configurations reduced inter-story drift and roof displacement by up to 79% and 88%. The study provides valuable guidelines for creating seismically resilient structural designs, substantially improving the safety and performance of RC buildings under seismic loads in mountainous terrain. The study aligns with building sustainable cities and resilient communities (Sustainable Development Goals (SDGs) 9 and 11), which minimize the damage to the infrastructure and reduce social losses in a community. Few studies have been done on the structural configuration of buildings on slopes, where limited guidelines were provided in the Indian Standards. The study includes soil–structure interaction and varies the location of the building based on practical scenarios that prove to be novel research to identify the best possible resilient structural configuration for building construction on slopes.